ANALISIS POTENSI ANGIN DAN SURYA DI UNIVERSITAS TEKNOLOGI SUMBAWA SEBAGAI STUDI KELAYAKAN PEMBANGKIT LISTRIK TENAGA HIBRID (PLTH) MENGGUNAKAN HOMER 3.16 - suhardin; Jaya , Ahmad; Maulidyawati , Desi; Hidayatullah, Muhammad (Program Studi Teknik Elektro, 2024)
Renewable energy is an energy source that can be obtained continuously from nature such as the sun, wind, water, geothermal, and biomass. According to the Directorate General of EBTKE in 2018, the total potential of renewable energy in Indonesia is 442 GW while the newly utilized is only 8.8 GW, therefore, there needs to be action to analyze the opportunity to add energy through calculations with Homer 3.16 software to see whether the Renewable Energy Power System can be applied. The purpose of this study is to find out how big the potential of wind and solar energy for the feasibility of building PLTH at Sumbawa University of Technology (UTS). The research method used is quantitative by collecting data in the form of solar irradiation, data on the load of electricity use around the UTS campus area and wind speed. Then the analysis method uses the HOMER software application. The results of HOMER 3.16 modeling, obtained that the modeling of the PLTH system in the UTS area at the condition of the average wind speed on the turbine of 3.13 m / s, solar irradiation received by solar panels of 5.59 kWh / m ^ 2 / day, then obtained a total production of 62.042 kWh of electrical energy per year with a total